MOVEMENT HISTORIES: A PRELIMINARY HISTORIOGRAPHY OF THE BRAZIL’S LANDLESS LABORERS’ MOVEMENT (MST) - Welch, Cliff (REVISTA NERA, 2012)
Founded in 1984, the Landless Rural Workers Movement of Brazil (MST) has been historicized in several recent publications. This review essay examines seven books that provide historical analysis of the movement. Published in English, Spanish, Portuguese, and Italian in the past six years, these books offer diverse assessments of MST history. The essay contrasts their interpretations of the movement’s origins, founding, consolidation, organization, and future prospects. As an institutionalized social movement with more than twenty years of history, the books prove that the MST merits the attention of historians.